Binding immunoglobulin 2 functions as a proviral factor for potyvirus infections in Nicotiana benthamiana - Widyasari, Kristin; Bwalya, John; Kim, Kook‐Hyung (Molecular plant pathology, 2023)
Infection of viruses from the genera Bromovirus, Potyvirus, and Potexvirus in Nicotiana benthamiana induces significant up‐regulation of the genes that encode the HSP70 family, including binding immunoglobulin protein 2 (BiP2). Three up‐regulated genes were knocked down and infection assays with these knockdown lines demonstrated the importance of the BiP2 gene for potyvirus infection but not for infection by the other tested viruses. Distinct symptoms of cucumber mosaic virus (CMV) and potato virus X (PVX) were observed in the BiP2 knockdown line at 10 days postagroinfiltration. Interestingly, following inoculation with either soybean mosaic virus (SMV) or pepper mottle virus (PepMoV) co‐expressing green fluorescent protein (GFP), neither crinkle symptoms nor GFP signals were observed in the BiP2 knockdown line. Subsequent reverse transcription‐quantitative PCR analysis demonstrated that knockdown of BiP2 resulted in a significant decrease of SMV and PepMoV RNA accumulation but not PVX or CMV RNA accumulation. Further yeast two‐hybrid and co‐immunoprecipitation analyses validated the interaction between BiP2 and nuclear inclusion protein b (NIb) of SMV. Together, our findings suggest the crucial role of BiP2 as a proviral host factor necessary for potyvirus infection. The interaction between BiP2 and NIb may be the critical factor determining susceptibility in N. benthamiana, but further studies are needed to elucidate the underlying mechanism. Interaction between binding immunoglobulin protein 2 (BiP2) and NIb of potyvirus promotes virus infections, making BiP2 a good candidate for gene modification to generate a resistant cultivar against potyviruses.